Allochrony in Atlantic Lumpfish: Genomic and Otolith Shape Divergence Between Spring and Autumn Spawners - Mathilde Horaud; Núria Raventós; Kim Præbel; Carles Galià‐Camps; Cinta Pegueroles; Carlos Carreras; Marta Pascual; Victor M. Tuset; Shripathi Bhat; Arve Lynghammar (Ecology and Evolution, 2025)
ABSTRACT Allochrony is a form of reproductive isolation characterized by differences in the timing of spawning and may play a crucial role in the genetic and phenotypic divergence within species. The Atlantic lumpfish (Cyclopterus lumpus) is known to spawn in spring and autumn. However, the role of allochrony on the genomic structure of this species has not been addressed. Here, by combining whole genome sequencing data and otolith shape of 64 specimens, we explore the evolutionary drivers of divergence in Atlantic lumpfish, focusing on spring and autumn spawners sampled at two well‐separated spawning grounds along the Norwegian coast. Overall, we identified pronounced genomic and morphologic differences between the two spawning groups. Genomic differences between the two groups were concentrated in three chromosomes, with a region of chromosome 1 encompassing the same single nucleotide polymorphisms (SNPs) driving differential season spawning for both localities, suggesting parallel responses. The functional analysis of the SNPs in this region revealed genes associated with responses to environmental stressors, possibly adaptations to seasonal variations at high latitudes. The morphological analysis of otoliths supported these findings, showing differences compatible with adaptations to seasonal light availability. The presence of genomic islands of divergence, alongside a general lack of differentiation across the mitochondrial genome, suggest recent and rapid selection processes potentially modulated by ongoing gene flow. This study underscores the importance of considering temporal genetic structures, particularly for species with bimodal spawning time, in conservation and management strategies to prevent overexploitation and optimize breeding programs.